Presupuesto vs costos reales de la Constructora Consvivisa S.A. año 2018 - Banchón Santillán, Ambar Stephania (2021)
This research is based on the problem regarding the management of costs and the construction budget of houses during the year 2018 of the construction company CONSVIVISA S.A. This analysis has been carried out with the information provided by the company with its cost department, the objective of this case study is focused on analyzing the budget items versus the real costs, to determine what are the actions carried out by those involved in the elaboration of the same and those carried out by those involved in the construction of the house. The research approach is quali-quantitative due to the objective to be analyzed and the research framework where it was possible to measure qualities and budgetary amounts and their incidence on costs, the research method used is the analytical method through which it will be analyzed. the information collected for its subsequent support, inductive and deductive methods were also used, relating them to the objective of the research and thus generating conclusions. The results of this research show that the budget items maintain differences between the costs executed for the construction of the houses due to weak controls and management by the people involved, these differences in most cases exceed the limits allowed by the company as internal policy.